Statistical properties of auditory behaviour outcome measures for children with hearing loss: a scoping review - Haris, Siti Munirah; Onwi, Nadwah; Mohamed Zain, Nor Azrita; Rahmat, Sarah; Othman, Basyariatul Fathi (Malaysian Medical Association (MMA), 2024)
Introduction: Various evaluation tools have been developed to track the growth of auditory-related behaviours of children with hearing loss during intervention. However, the reliability and validity of currently available outcome measures remain uncertain due to the lack of information on their psychometric properties. A lack of reliable outcome measures may jeopardise intervention quality and affect these children’s listening skills progression. This scoping review aims to explore the mechanics of producing or developing an outcome measure either completely new or adapted from the original version that is considered as having robust statistical properties